Kartun : studi tentang permainan bahasa - Wijana, I Dewa Putu, 1956- (Jogjakarta : Ombak, 2003)
Discourse of Indonesian cartoons
Includes bibliographical references (p. 307-315) and index
Keywords: Caricature and cartoons -- Indonesia -- History criticism